Migratory behaviour and survival rates of wild northern Atlantic salmon Salmo salar post-smolts: effects of environmental factors - Thorstad, EB; Davidsen, Jan Grimsrud; Økland, F.; Rikardsen, Audun H.; Halttunen, Elina; Letcher, B.H; Næsje, Tor; Skardhamar, Jofrid (Universitetet i Tromsø, 2009)
Poster presentation at the Eight Conference on Fish Telemetry held in Europe, Umeå, Sweden, 14-18 September 2009